2012
DOI: 10.3389/fpls.2012.00121
|View full text |Cite
|
Sign up to set email alerts
|

Cell wall mechanics and growth control in plants: the role of pectins revisited

Abstract: How is the extensibility of growing plant cell walls regulated? In the past, most studies have focused on the role of the cellulose/xyloglucan network and the enigmatic wall-loosening agents expansins. Here we review first how in the closest relatives of the land plants, the Charophycean algae, cell wall synthesis is coupled to cell wall extensibility by a chemical Ca2+-exchange mechanism between Ca2+–pectate complexes. We next discuss evidence for the existence in terrestrial plants of a similar “primitive” C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
201
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(210 citation statements)
references
References 39 publications
4
201
0
5
Order By: Relevance
“…A recent study that combined extensometry with atomic force microscopy and different forms of cell wall strain showed that both cellulose microfibrils and matrix polymers, predominantly pectins, bear the tensile load of elastically stretched onion walls (Zhang et al, 2017). This confirms the mechanical significance of the matrix at the molecular scale and adds impetus to recent interest in the state of pectins in growing cell walls and the need for better models of cell wall mechanics (Peaucelle et al, 2012;Xiao et al, 2014;Levesque-Tremblay et al, 2015).…”
Section: Discussionmentioning
confidence: 58%
“…A recent study that combined extensometry with atomic force microscopy and different forms of cell wall strain showed that both cellulose microfibrils and matrix polymers, predominantly pectins, bear the tensile load of elastically stretched onion walls (Zhang et al, 2017). This confirms the mechanical significance of the matrix at the molecular scale and adds impetus to recent interest in the state of pectins in growing cell walls and the need for better models of cell wall mechanics (Peaucelle et al, 2012;Xiao et al, 2014;Levesque-Tremblay et al, 2015).…”
Section: Discussionmentioning
confidence: 58%
“…The proposed mechanisms of PME action in these processes can be summarized as follows: (1) creating an acidic environment within the cell wall as a result of deesterification of pectins, thus promoting cell wall extension or growth, perhaps through the modulation of expansins (see above); (2) facilitating the hydrolysis of polygalacturonic chains by polygalacturonases (Wakabayashi et al, 2003); and (3) promoting the formation of calcium cross linkages (through demethylation of pectins) that ultimately change the state of the pectin matrix by generating free carboxyl groups that are able to bind Ca 2+ (Micheli, 2001;Peaucelle et al, 2012).…”
Section: Pme Activity Plays a Role In Arabidopsis Seed Germinationmentioning
confidence: 99%
“…Demethylesterification of cell wall pectins is mediated by pectin methylesterases (PMEs; EC 3.1.1.11). PME activity thus alters cell walls and, hence, mediates various physiological and biochemical processes in plants, including elongation growth and fruit ripening (for review, see Micheli, 2001;Wolf et al, 2009;Peaucelle et al, 2012). Some of the changes in the biomechanical properties of cell walls resulting from PME action are mediated through an increased susceptibility of homogalacturonans to polygalacturonases (Wakabayashi et al, 2003) and modulation of the activity of cell wall expansins through a decrease in cell wall pH (Moustacas et al, 1991;McQueen-Mason and Cosgrove, 1994).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pectinesterase (PME) was identified as the major protein involved in cell wall metabolism. The demethylation of cell wall pectins is mediated by pectin methylesterases, whose activity alters cell walls and mediates various physiological and biochemical processes in plants, including elongation growth, water uptake, and fruit ripening (Peaucelle, Braybrook, & Hofte, 2012).…”
Section: Protein Biologymentioning
confidence: 99%